Underwater ejection multifield coupling model and response characteristics. (15th April 2023) - Liu, Haotian; Li, Shangming; Fu, Debin; Bi, Fengyang
Abstract: This article presents a numerical simulation analysis of the ejection process of a rigid projectile under the coupling effect of a support structure, ejection gas and transverse flow in a launch tube. Based on the computational fluid dynamics method and nested dynamic mesh technique, the dynamic response model of the support structure is used to simulate the deformation loads of the support structure inside the tube and construct a multifield coupled model for underwater ejection. Through computational analysis, we focus on the evolution characteristics of the multiphase flow field during the ejection process, the development mechanism of the bubble at the tube outlet, and the trajectory and load response characteristics of the projectile. In addition, the effects of different launch conditions, such as transverse flow velocity and interphase heat and mass transfer effects, on the projectile ejection process are also analyzed. The results show that the established model can effectively characterise the ejection motion process of the projectile. The impact of the lateral flow causes drastic changes in the motion displacement and velocity of the projectile as well as the rotation angle and rotation angular velocity. Furthermore, the interphase heat and mass transfer effects have less influence on the ejection process of the projectile due to the temperature change of the high-temperature ejected gas caused by the intermittent interface between the bubble and the aqueous medium. Highlights: The loading situation of the projectile underwater ejection process is analyzed. A multi-field coupled calculation model for underwater ejection is established. The main reason for the change of the thermodynamic parameters of the ejection gas in the barrel is found to be the intermittent bubble interface. The multiphase flow field variation and dynamic response characteristics of the projectile ejection process are clarified. The influence of different ejection conditions on the underwater ejection process is studied.